Craniofacial changes from 13 to 62 years of age. (28th March 2022) - Al-Taai, Nameer; Persson, Maurits; Ransjö, Maria; Levring Jäghagen, Eva; Fors, Ronny; Westerlund, Anna
Summary: Background: In long-term studies of orthodontic, orthognathic, and prosthodontic treatments, control subjects are needed for comparison. Objectives: To study the craniofacial (skeletal, soft tissue, and dental) changes that occur in untreated subjects with normal occlusion between 13 and 62 years of age. Materials/Methods: Thirty subjects with a Class I normal occlusion and harmonious facial profile were studied. X-ray examinations were performed at 13 (T1), 16 (T2), 31 (T3), and 62 (T4) years of age, and data were obtained from cephalograms. In total, 53 angular and linear parameters were measured using superimposition-based and conventional cephalometric methods to describe the craniofacial changes. Results: The jaws showed significant anterior growth from T1 to T2, and significant retrognathism from T3 to T4. The anterior face height and jaw dimensions increased significantly until T3. Significant posterior rotation of the mandible and opening of the vertical jaw relation, in addition to significant retroclination of the incisors and straightening of the facial profile, were found from T3 to T4. Limitations: Given the small sample size at T4, it was not possible to analyse the gender dimension. Conclusions/Implications: Craniofacial changes continue up to the sixth decade of life. These changes are consistent, albeit to a lesser extent, with the adolescent growth patterns for most of the studied parameters, with the exceptions of incisor inclination, sagittal jaw position, vertical jaw relation and inclination, and posterior face height.